English language teachers’ readiness for the application of technology towards fourth industrial revolution demands - Norizan Abdul Razak,; Alakrash, Hussien; Yasmin Sahboun, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Using technology has proven to be effective in teaching and learning the English language. With the emergence of the fourth industrial revolution mentioned in Davos 2016, the use of technology in learning and teaching the English language needs to be explored. There is an increasing pressure exercised by the advancements of technology in education. Recently, the use of technology for teaching has become an integral part of successful learning and teaching languages in many parts of the world. Researchers suggested that successful implementation and usage of educational technologies depends mainly on the willingness of teachers as they are the main component in the classroom, who eventually decide on whether to integrate them or not and on how they are to be used in the classroom. The purpose of this qualitative study, therefore, is to measure the English language teachers’ readiness and willingness to use the technology in teaching the English language in the era of the fourth industrial revolution. Ten in-service English language teachers participated in the structured and semi-structured interviews. The findings of the interview showed that the English language teachers are not ready yet to use the technology in teaching the English language some ideas were revealed through the interviews 1) traditional and cultural ways of teaching 2) the understanding and attitudes towards technology 3) obstacles hinder teachers from using technology. Finally, the paper presented a number of implications and recommendations that include providing training programs for teachers and forums with experts of the fourth industrial revolution. The policy must be formulated to encourage teachers to use technology to improve the Arab teachers and students’ use of the new technology in teaching and learning spaces.